2016
DOI: 10.1093/jxb/erw062
|View full text |Cite
|
Sign up to set email alerts
|

Root phenology in a changing climate

Abstract: Plant phenology is one of the strongest indicators of ecological responses to climate change, and altered phenology can have pronounced effects on net primary production, species composition in local communities, greenhouse gas fluxes, and ecosystem processes. Although many studies have shown that aboveground plant phenology advances with warmer temperatures, demonstration of a comparable association for belowground phenology has been lacking because the factors that influence root phenology are poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 105 publications
2
120
0
2
Order By: Relevance
“…). Root growth is endogenously regulated by the timing of C availability and tradeoffs among competing plant sinks (Comas et al ., ) and is exogenously influenced by climatic and edaphic variables (Abramoff & Finzi, ; Radville et al ., ,). A field experiment on root dynamics in a temperate steppe, for example, found that increased temperature and precipitation individually or interactively affected annual root production (Bai et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Root growth is endogenously regulated by the timing of C availability and tradeoffs among competing plant sinks (Comas et al ., ) and is exogenously influenced by climatic and edaphic variables (Abramoff & Finzi, ; Radville et al ., ,). A field experiment on root dynamics in a temperate steppe, for example, found that increased temperature and precipitation individually or interactively affected annual root production (Bai et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…C availability and tradeoffs among competing plant sinks) and exogenous factors (e.g. temperature, moisture, and nutrient availability) (Comas et al ., ; Du & Fang, ; Radville et al ., ,). Empirical studies of root initiation and cessation are rare, but these two phenophases may be controlled mostly by soil temperature and timing of C availability (Radville et al ., ), and peak root growth may represent tradeoffs among competing plant sinks (Comas et al ., ; Artacho & Bonomelli, ; Radville et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Arctic, the belowground plant biomass exceeds its aboveground counterpart (Mokany et al, 2006; Iversen et al, 2015; Wang et al, 2016a) and therefore represents an important component of soil nutrient cycling and net ecosystem C budget (Iversen et al, 2015). As concluded by Blume-Werry et al (2016) neither the knowledge from non-Arctic ecosystems, nor projections of aboveground to belowground production, reflect seasonal dynamics of root growth in arctic plant communities and limited data is available on root phenology in this region (Radville et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…We conclude that in a northern temperate climate, the 37 overwintering strategies of roots of herbaceous monocots are binary: either avoidance or 38 tolerance of the long unfavourable season, similar to deciduous and evergreen leaves 39 among woody plants. Roots root phenology limits our understanding of the relationship between root turnover 61 strategies and environmental conditions (Radville et al 2016). 62…”
mentioning
confidence: 99%